Attributable Costs of Postoperative Atrial Fibrillation among Patients Undergoing Cardiac Surgery - Pattamawan Kosuma; Sitichok Wachirasrisirikul; Arom Jedsadayanmata (Cardiology Research and Practice)
Background. Postoperative atrial fibrillation (POAF) is the most common complication among patients undergoing cardiac surgery. However, data on the economic burden and resource utilization associated with POAF in Asian population are limited. The present study aimed at estimating medical costs attributable to POAF after cardiac surgery in Thai population. Methods. We analysed data from claims database of patients who underwent valve replacement, coronary artery bypass grafting (CABG), or a combination of both procedures at a tertiary-care, academic hospital in Thailand. Multiple linear regressions of log-transformed costs were developed with the occurrence of POAF and preoperative patient characteristics as covariates. After back-transformation to the original scale, costs attributable to POAF were estimated from the mean difference between patients with and without POAF. Results. Of 711 patients undergoing cardiac surgery, 241 (30.94%) developed POAF over a median hospitalization of 10 days. Patients with POAF utilized more resources than those without POAF. POAF was an independent predictor and increased cost by 23% in linear regression model. On average, patients with POAF had higher medical costs than those without POAF (269,000 versus 218,999 Thai Baht (THB)) with a mean difference of 50,000 THB (1,667 USD). The difference was observed in patients undergoing isolated valve surgery (47,761 THB (1,592 USD), 95% CI: 39,809–55,712), CABG (50,865 THB (1,696 USD), 95% CI: 37,233–64,496), and a combination of both procedures (72,287 THB (2,410 USD), 95% CI: 49,910–94,405). Conclusions. In a single-institution study in Thailand, POAF is associated with increased resource use and medical costs among patients undergoing cardiac surgery. Effective strategies to prevent POAF should be implemented to reduce its economic burden.